Durability study at different age groups of planted Acacia mangium superbulk species of Sarawak - Nurizatulsima, Binti Abdul Aziz. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Some of timber supply for natural durable, cannot meet the demand for timber industry because naturally durable timber usually takes too long time to grow which is associated to heavy and medium hardwood. To overcome this problem, the initiative has been put in place to select quality breed species of light hardwood of Acacia mangium known as Acacia mangium Superbulk which has criteria with fast growth rate and higher resistance to heart rot had been planted in Sarawak. Nevertheless, ability and durability of wood are an inescapable wood quality in a wood industry that should be considered. Therefore, this research is conducted to study the durability of planted Acacia mangium Superbulk to identify the potential age group that more resistant to fungus attack as a recommendation for utilization in the timber industry. The accelerated decay test is conducted to identify the natural durability classification at different age of Acacia mangium Superbulk. All specification of accelerated decay test is accordance to ASTM Designation: D2017-05. There are two types of test fungus use in this study which is white rot fungus Coriolus versicolor and brown rot fungus Gloeophyllum trabeum. The preparation of media culture for durability test are using agar block method. Then, sample blocks of Acacia mangium Superbulk age of 7, 10, and 13-year-old are introduced into respective fungus for testing in 16 weeks and the test is can be terminated after 50% of weight loss obtained from the reference sample. Based on the finding, Acacia mangium Superbulk which is categorized under Light Hardwood (LHW) according to Malaysian Standard has been classified under durability class of resistant. The result from white rot fungus Coriolus versicolor has shown that, 10-year-old was classified as resistant while age 7 and 13-year-old were classified as least moderately resistant to white rot fungus attack. Meanwhile, result from brown rot fungus Gloeophyllum trabeum has shown that, all three age group were classified as highly resistant to brown rot fungus attack. Therefore, in conclusion white rot fungus is more aggressively attack Acacia mangium Superbulk than brown rot fungus. Age 10 years old Acacia mangium Superbulk is the most suitable selection of tree with higher resistant to fungus attack.